Reform for The Development of Digital Arabic Language Teaching Materials Based on Constructivism Theory - Nurhadi Nurhadi; Danial Hilmi (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2022)
The purpose of this study was to provide an overview of the formulation of the development of digital Arabic teaching materials by including learning targets that are in line with the formation of active learning abilities. This study used a qualitative approach with data related to information about the pattern of developing website-based digital teaching materials. Data collection techniques used were interviews, observation, and documentation studies. As for the data analysis done by collecting, condensing, displaying data and concluding. Based on the results of the study, it was found that the development of digital teaching materials on UIN Maulana Malik Ibrahim completed adequate audio-visual-based applications integrated with the teaching materials and applied by new students through distance learning and used to develope their language skills through a constructivist learning approach that is integrated into the textbook.